Fast and safe microwave-assisted glass channel-shaped microstructure fabrication1. Issue 11 (7th June 2015) - Zacheo, A.; Zizzari, A.; Perrone, E.; Carbone, L.; Giancane, G.; Valli, L.; Rinaldi, R.; Arima, V.
<x xml:space="preserve">Abstract</x> Microwave-assisted wet etching intensifies the glass etching action under safe working and finely monitored operative conditions and it produces smooth deep channels in short processing times with reduced underetching effects.